Functionalization Effect on Polymer Nanocomposite Coatings Based on TiO2–SiO2 Nanoparticles with Superhydrophilic Properties - Arturo Román Vázquez-Velázquez (Nanomaterials, 2018)
In this study, a novel binary nanocomposite system based on TiO2-SiO2 was functionalized with trimethylolpropane triacrylate (TMPTA) and characterized by XPS and XRD. Results revealed that TiO2-SiO2 nanoparticles were covalently functionalized. Functionalized nanoparticles at low concentrations (0.1 wt % and 0.5 wt %) were dispersed in acrylic acid acting as a polymer matrix. Nanocomposite coatings analysis demonstrate to achieve superhydrophilic properties as well as very good optical characteristics. Water contact angle characterization showed the functionalization effect by achieving a superhydrophilic behavior with a contact angle less than 5°. UV-Vis measurements demonstrated high optical transmittance above 95% for the coatings. Based on the obtained results a mechanism describing the chemical interactions of the constituents responsible for the synergy in the nanocomposite as well as the morphological play role in the behavior are presented.